Analysis of Labor Productivity at the Pottery Craft Industry Center in Masbagik Timur Village, Masbagik District, East Lombok Regency - Ahmad Majdi; Akung Daeng; Tuti Handayani (Westscience Press, 2025)
This study is entitled